Geographic Information Systems Practice Midwife In Merauke Regency Android-Based Method Using Spherical Law of Cosines - Tatik Melinda Tallulembang (International Journal of Science, Technology & Management, 2021)
Health is a resource for the daily life of the community. Because without health, a person can not run the activity with the good. To that end, the society can not be separated from the figure of health that play a role in manifesting the life of a healthy society as a midwife. One of the reasons people really need a midwife is the cost of the examination or the cost of labor is affordable. Therefore, it is needed a Geographic Information System Midwife Practice in Merauke Regency Android-Based Method Using Spherical Law of Cosines can help and facilitate user to search, and know the location of the midwife practice and service information available at the place of such practices as well as the closest distance to the user. Geographic Information system Midwife Practice in Merauke Regency Android Based on the design by using Eclipse with the java programming language, and using a MySQL database. The method used to search the nearest distance of the user with the location of the midwife practice using the method of Spherical Law of Cosines, and the method of testing using the method of blackbox and questionnaires. The result of this research is to produce a geographic information system application based on android to handle mapping the location of the midwife practice as well as data information midwife online which is accessible to the public in Merauke Regency.